USING FAIRY TALES TO DEVELOP CREATIVE THINKING AND SPEAKING SKILLS - Sattorova Nilufar Bahodir qizi (Modern American Journals, 2025)
This article discusses the development of creative thinking and speaking skills among primary school learners through the use of fairy tales. Fairy tales, as engaging and culturally rich materials, expand learners’ imagination and create a natural language environment for oral communication. The findings of the study show that storytelling, role-playing, and fairy tale-based activities help students enrich their vocabulary, improve fluency, and build confidence in expressing their ideas in English.
Keywords: fairy tales, creative thinking, speaking skills, storytelling, primary education, motivation